Cytoplasmic Drosha activity generated by alternative splicing. Issue 21 (28th July 2016) - Dai, Lisheng; Chen, Kevin; Youngren, Brenda; Kulina, Julia; Yang, Acong; Guo, Zhengyu; Li, Jin; Yu, Peng; Gu, Shuo
Abstract: RNase III enzyme Drosha interacts with DGCR8 to form the Microprocessor, initiating canonical microRNA (miRNA) maturation in the nucleus. Here, we re-evaluated where Drosha functions in cells using Drosha and/or DGCR8 knock out (KO) cells and cleavage reporters. Interestingly, a truncated Drosha mutant located exclusively in the cytoplasm cleaved pri-miRNA effectively in a DGCR8-dependent manner. In addition, we demonstrated that in vitro generated pri-miRNAs when transfected into cells could be processed to mature miRNAs in the cytoplasm. These results indicate the existence of cytoplasmic Drosha (c-Drosha) activity. Although a subset of endogenous pri-miRNAs become enriched in the cytoplasm of Drosha KO cells, it remains unclear whether pri-miRNA processing is the main function of c-Drosha. We identified two novel in-frame Drosha isoforms generated by alternative splicing in both HEK293T and HeLa cells. One isoform loses the putative nuclear localization signal, generating c-Drosha. Further analysis indicated that the c-Drosha isoform is abundant in multiple cell lines, dramatically variable among different human tissues and upregulated in multiple tumors, suggesting that c-Drosha plays a unique role in gene regulation. Our results reveal a new layer of regulation on the miRNA pathway and provide novel insights into the ever-evolving functions of Drosha.